2019
DOI: 10.1039/c9fo00444k
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic strains improve high-fat diet-induced hypercholesterolemia through modulating gut microbiota in ways different from atorvastatin

Abstract: Probiotics exert additional favorable effects on gut microbiota, making them excellent potential complements to cholesterol-lowering drugs like ATO.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…In previous studies where golden hamsters were exposed to unpredictable chronic mild stress or LAB administration, ingestion of probiotics significantly decreased the body weight gain ( 66 68 ). However, in the studies where feeding was unrestricted but monitored, probiotic intervention had no effect on body weight gain ( 38 , 39 , 66 , 69 ), which was consistent with our findings here. Remarkably, Lactobacillus fermentum ZJUIDS06 exhibited cholesterol-lowering effect while Lactobacillus plantarum ZY08 did not have such effect.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In previous studies where golden hamsters were exposed to unpredictable chronic mild stress or LAB administration, ingestion of probiotics significantly decreased the body weight gain ( 66 68 ). However, in the studies where feeding was unrestricted but monitored, probiotic intervention had no effect on body weight gain ( 38 , 39 , 66 , 69 ), which was consistent with our findings here. Remarkably, Lactobacillus fermentum ZJUIDS06 exhibited cholesterol-lowering effect while Lactobacillus plantarum ZY08 did not have such effect.…”
Section: Discussionsupporting
confidence: 91%
“…In previous reports, the cholesterol-lowering intervention strategies used in hyperlipidemic rodents increased the relative abundance of Lactobacillus or Bifidobacteria and decreased the ratio of Firmicutes to Bacteroides ( 39 , 73 75 ). However, interventions used in this study did not have such effects ( Figure 8B ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The Chao1 and Shannon indices showed that the species richness and the evenness of the intestinal bacteria in the Drosophila on a standard diet were different to those on a probiotics-supplemented diet. These results support the conclusions of previous studies, which suggested that dietary probiotic administration can increase gut bacterial diversity [76][77][78]. These changes in species diversity can be considered to be beneficial effects of the probiotic combination on Drosophila, because species-rich microorganisms are more resistant to pathogen invasion, more efficient at resource utilization, and make the intestinal ecosystem more stable [79,80].…”
Section: Discussionsupporting
confidence: 89%
“…Genomic DNA extraction and library construction were performed at Shenzhen BGI Technology following a previously reported protocol ( 18 ).…”
Section: Methodsmentioning
confidence: 99%